2011
DOI: 10.1016/j.jpeds.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Psoriasis and Elevated Blood Lipids in Overweight and Obese Children

Abstract: Objective-To investigate whether obesity and cardiovascular risk factors are associated with psoriasis in children and adolescents.Study design-For this population-based, cross-sectional study, measured weight and height, laboratory data, and psoriasis diagnoses were extracted from electronic medical records of 710,949 patients 2-19 y enrolled in an integrated health plan. Weight class was assigned based on body mass index-for-age.Results-The OR for psoriasis was 0.68, 1.00, 1.31, 1.39, and 1.78 (95%CI 1.49-2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
3
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 36 publications
1
86
3
4
Order By: Relevance
“…In addition, it has been demonstrated that there is a positive association between childhood psoriasis and overweight (5,6). A recent study by Koebnick et al (7) showed that obesity was associated with higher odds of psoriasis in children and adolescents. Other epidemiological data indicate that the greatest risk of myocardial infarction and incident diabetes mellitus is observed in young adult patients with severe psoriasis (8,9).…”
Section: Short Communicationmentioning
confidence: 99%
“…In addition, it has been demonstrated that there is a positive association between childhood psoriasis and overweight (5,6). A recent study by Koebnick et al (7) showed that obesity was associated with higher odds of psoriasis in children and adolescents. Other epidemiological data indicate that the greatest risk of myocardial infarction and incident diabetes mellitus is observed in young adult patients with severe psoriasis (8,9).…”
Section: Short Communicationmentioning
confidence: 99%
“…The risk profile for our younger patients is still under investigation, but a pattern linking psoriasis and the metabolic syndrome seems to be emerging [1,8,9,13,20,[28][29][30][31][32][33][34].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Multiple authors, including Au et al [31], Koebnick et al [32], and Volf et al [33], state that pediatric psoriasis patients should be monitored for cardiovascular risk factors and, if found at risk, should receive preventive interventions [34]. tywnie wp艂ywa na jako艣膰 偶ycia pozosta艂ych cz艂onk贸w rodziny [1,5,[24][25][26].…”
Section: Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric psoriasis differs from adult onset psoriasis in types of environmental triggers, with trauma, stress, and bacterial infection being the most common pediatric disease triggers [ 1 , 3 ], while drug-reactions, smoking, alcohol use, and underlying HIV infection are triggers more common in adulthood [ 4 ]. Recently, obesity and the metabolic syndrome have been linked to both pediatric and adult psoriasis [ 5 ]. Treatment options are similar for adult and pediatric psoriasis patients, although therapy selection for pediatric psoriasis varies according to patient age and is limited by the fact that systemic treatments for pediatric psoriasis are off-label.…”
Section: Introductionmentioning
confidence: 99%